(untitled) (The Journal of Knowledge and Innovation, 2023)
शिक्षा दिने मन्त्रदिने , जन्मदिने , विवाह गरी छोरी दिने शिक्षक हुन् ।यस्तो मान्यता नेपाल र भारतले राख्तछ । विश्वलाई यस्तै उपदेश दिन्छन् । यी उल्लेख्य व्यक्तित्वबाट जीवनभर शिक्षा पाइन्छ । यिनीहरूले ज्ञान बाँड्छन् । अनुशासित र आचारवान् बन्न र बनाउन सिकाउँ छन् । जे जोबाट सिक्छ ,सिकिन्छ शिक्षा त्यही हो । यसले आफ्नो जरा खोज्छ । सभ्यताको मूलथलो वेदमा लगे र जोड् दछ । वेद ज्ञानको ढिक्को, ढिम्को, ढिस्को, कुइनेटो हो । यो विज्ञान हो । यसका गर्भमा विज्ञानका फाल्साफाल्सा लुकेर रहेका छन् । अविद्याले भौतिक सुख हुन्छ । विद्याबाट अमृतत्व पाइन्छ । शुक्लयजुर्वे द. अ.३९ मन्त्र १४ले भन्छ अविद्ययामृत्युन्तीत्वा विद्ययामृतमश्नुते । मान्छे त्यसैे स्वतः शिक्षित बन्दैन । मानिस पशुसरह व्यवहार गर्दागर्दै विस्तारै आमा बावु र गुरुहरूद्वारा मौखिक या मानसिक खाली कागज जस्तो दिमागमा ज्ञानको भण्डार भरिएको शिक्षा पाउदै गएपछि मात्र मान्छे शिक्षित बन्छ । शिक्षित भएपछि शिक्षक बन्छ । विद्याविहीन पशु भनिन्छ । विद्याको अर्थ ज्ञान हो , अविद्या अज्ञान हो । ज्ञानी हुनेले ज्ञान पाएपछि, शिक्षा दिनेले दिएपछि ,शिक्षा लिनेले लिएपछि मात्र शिक्षण हुन्छ । यो दिने र लिने बीचको सौदा या व्यपार हो । हो यो विक्रेता र क्रेता बीचको बजार व्यवस्था हो । शिक्षणले मानिसलाई नियम, नीति, सीप सिकाएर यो गर्न हुने यो गर्न नहुने को नीतिले बाँध्ने गर्छ । व्यवहारिक, व्यवसायिक, सीपले र कलायुक्त ज्ञानले सामाजिक प्राणी बनाउँछ । आनीबानीमा परिवर्तन गरिदिन्छ । स्वभाव र प्रवृत्तिमा सुध्रिने , सुधार्ने मौका जुटाई दिन्छ । शिक्षणले विशद महान र उत्तम भावना प्रज्वलित गराउँछ । विद्याव्यसनी र निष्ठावान् बनाउँ छ । अञ्चल, जनपद , भूगोलले , राजनीति, अर्थनीति, धार्मिक जातीय, पारिवारिक कर्तव्यको बोध पनि शिक्षणबाटै हुन्छ । प्राकृतिक, परिस्थितिक, प्रातस्मरणीय चिन्तक, लोकमान्य , लोकविश्वास, वित्तव्यवसायको संरक्षण, सम्बध्र्दनको रक्षागर्ने सीपको जानकारी शिक्षणबाटै पाउँ दछ । धर्म, चाडवाड, मेला मठ, मन्दिर ,मस्जिद,गुम्वा, गिर्जाघरको उत्खनन् परिचय, सूचनाहरूका तालिकाको कार्य र ज्ञान गर्न सक्दछ । ज्ञान–विज्ञान, जल, जमिन, खगोल, मौसम, इत्यादि बारे नयाँ धारण र नयाँ चिन्तन गर्ने पद्धति शिक्षणले सिकाउँंछ । आत्मा परमात्मा, ईश्वरलाई अलगअलग व्याख्या र विश्लेषण गरी जीवलाई आजाद गर्ने सीप शिक्षणबाट हुन्छ । शिक्षित र सभ्य मानिस सुसंस्कृत हुन्छ भन्ने मान्यता थाहाँँ पाउँछ । वेदका ऋचा मन्त्रबाट उदात्त अनुदात्त र स्थरितबाट शिक्षाको प्रार्दुभाव भयो भन्ने थाहा पाउँदछ । । ऋचाको शिक्षण हजारौं हजार वर्षदेखि हुदै आयो । सुनेका भरमा शिक्षण गरिदा वेद श्रुति कहलियो । सम्झे का कुराहरूको टिपोट र नोट स्मृति भए । श्रुति स्मृतिहरूमा तर्क शक्ति, विचार निर्माण गर्ने क्षमताको अभिवृद्धि, भावना र कल्पनाको स्वभावमा लहरिने सीप ज्ञान विज्ञानको छे लोखे लोपन आदि लदबदे रसिलो ज्ञान हुन्छ । यी सवै दर्शनलाई एकबाट अर्कोमा पुर्याउने साधन शिक्षक हुन । पुस्तकालय वाचनालय, अभिलेखिकृत, श्रोतकेन्द्र, श्रव्यदृष्य, आदि विद्युतीय सामग्रीको माध्यमले प्राविधिक विचारहरूको प्रक्षेपण शिक्षकले शिक्षार्थीमा गर्छ । माईक्रोफिल्म, कम्प्युटर, इन्टरनेट, डिजिटल पुस्तकालय, इपुस्तकालय, भच्र्युअललाईब्रेरी,आदिले पनि ज्ञान र विचारको ओसार पसार गर्छन् । एफ.डब्लुलुका अनुसार शिक्षक कक्षामा पस्नु पूर्व नै विद्यार्थीमा ज्ञानप्रतिको प्रेम र मोह जाग्न जगाउन सक्नुपर्दछ । भोलि शिक्षण गर्ने शिक्षक कक्षा नछुटोस भन्ने भाव विद्यार्थीमा जाग्नु पर्दछ । यस्तो सिकाईले ज्ञानलाई सम्वध्र्दन र पथ प्रदर्शन गर्दछ । प्राचीन र आधुनिक परिपेक्ष्यमा ज्ञान र प्रविधिको कुन्जी नेपाल र भारत का शास्त्र् , ग्रन्थ् , पुस्तक, पुस्तिकामा कैद भएका छन । Education is a mantra in itself, giving birth, getting married, and having children, they all contribute to becoming a teacher. This belief is held by Nepal and India. It imparts such teachings to the world. These notable personalities provide education throughout their lives. They share knowledge. They learn to be disciplined and well-behaved. What one learns from any job is education itself. It searches for its own roots. It is found in the Vedas, which add to its essence. Vedas are the essence, core, and foundation of knowledge. This is science. It encompasses the philosophy of science. Ignorance leads to materialistic pleasure, while knowledge leads to immortality. Shukla Yajur Veda, 3.39.14, says, "From ignorance, one experiences death, and from knowledge, one experiences immortality." A person does not become educated by themselves. Humans are like animals, engaging in behavior, expanding through parents and teachers, filling their minds with knowledge. Only then does a person become educated. After becoming educated, one becomes a teacher. An uneducated person is called an animal. Knowledge means wisdom, and ignorance means lack of knowledge. When one attains knowledge, when one imparts education, and when one receives education, only then does teaching occur. This exchange between giving and receiving is like a business transaction or a trade. It is the market system between the seller and the buyer. Education binds humans with rules, policies, and traditions. It shapes them into practical, business-oriented, disciplined, and artistic individuals, who become social beings. It brings about changes in society. It provides opportunities for improving one’s nature and behavior. Education ignites clear and noble sentiments. It makes one addicted to knowledge and loyal. It encompasses the knowledge of regions, provinces, geography, politics, economics, religious and ethnic duties. It also imparts knowledge of natural, environmental, memorable thinkers, popular beliefs, and the preservation of financial transactions and relationships. It can provide an introduction to various aspects such as religion, festivals, temples, mosques, monasteries, churches, memorials, and the organization of information. Education can teach new concepts and new ways of thinking about knowledge and science related to elements like knowledge-science, water, land, astronomy, weather, etc. It enables the understanding and analysis of the soul, the supreme soul, and God, thus freeing individuals. It is believed that an educated and civilized person is well-mannered. The emergence of education from the hymns and mantras of the Vedas has been known for thousands of years. When education is imparted based on what is heard, it is called Vedic instruction. The tips and notes of comprehension became memories. In the hymns and memories, the power of reasoning, the ability to construct ideas, the nature of emotions, and the flow of creative knowledge are revealed. All these philosophies converge into one from another, making the teacher the medium. Through libraries, reading rooms, archives, audiovisual centers, listening and watching, technical ideas are transmitted by teachers to students. Even microfilm, computers, the internet, digital libraries, e-books, virtual libraries, etc., spread knowledge and ideas. According to F. W. Taylor, the teacher must have the desire to instill love and fascination for knowledge in the students even before entering the classroom. Tomorrow, the teacher who teaches will not be separated from the students. Such a feeling needs to be awakened in the students. This teaching inspires knowledge and guides the path. In the context of ancient and modern perspectives, knowledge and technology are the keys to development.